An Extension of Kantorovich Inequality for Sesquilinear Maps (European Journal of Pure and Applied Mathematics, 2017)
By using sesquilinear map we generalize some operator Kantorovich inequalities.Our results are more extensive than many previous results due to Mond and Pecaric.
Keywords: Kantorovich inequality; positive linear map; inequality.